Parental Beliefs and Experiences about Their Children's Epilepsy after Starting the Ketogenic Diet in Riyadh, Saudi Arabia - Alqahtani, Mohammed M. J.; Mahmoud, Adel A. H. (Journal of Pediatric Neurology, 2016)
Objectives The aim of this qualitative study is to examine the attitude and experience of parents with epileptic children regarding the disease after ketogenic diet intervention.Methods The qualitative study used semi-structured one-to-one interviews with parents of epileptic children during their ketogenic diet intervention between June 1, 2010, and July 31, 2014. The parents of 30 children with epilepsy treated in King Fahad Medical City, Riyadh, Saudi Arabia, were included in final analysis.Results Parents reported that evil eye, spirit possession, and black magic could be the main cause of their children's epilepsy. Cultural beliefs dictate the way parents seek help. The most frequent interventions reported were going to Sheikh to read the Quran, use holy water, and black onion seeds. After starting and maintaining a ketogenic diet, there was a significant positive attitude towards the scientific ways of treating epilepsy. Parents showed a positive attitude towards the ketogenic diet intervention. Improved cognition, walking, mood, increased vocabulary, better sleep, and medication reduction were the major improvements reported in our sample set even when parents were holding cultural beliefs about epilepsy; they changed their opinion positively after the ketogenic diet.Conclusion Cultural beliefs, despite being deeply rooted in the minds of parents are still amenable to change. Professionals should carefully discuss parental beliefs and expectations in advance of ketogenic diet initiation to rectify the false ones. This study suggests that advice, support, and information, which amend culture beliefs, are recommended.
Keywords: neuropsychology; cognition; ketogenic diet; epilepsy